RADI-40. STEREOTACTIC RADIOSURGERY FOR BRAINSTEM METASTASES: AN ANALYSIS OF SINGLE FRACTION AND MULTI FRACTION TECHNIQUES. (12th August 2019) - Nack, Elana; Iyengar, Varun; Yu, Esther; DiPetrillo, Thomas; Kinsella, Timothy; Wazer, David; Cielo, Deus; Toms, Steven; Hepel, Jaroslaw; Koffer, Paul
Abstract: PURPOSE: Utilization of stereotactic radiosurgery (SRS) for brainstem metastases (BSM) is increasing. Multi-fraction SRS (MF-SRS) is a potential means of obtaining therapeutic gain while limiting toxicity. However, most available data assesses only single-fraction SRS (SF-SRS). This study aims to evaluate the efficacy and safety of SF-SRS and MF-SRS for BSM. METHODS: Data was retrospectively collected for patients with BSM treated with SRS between 2003–2018 at a single institution. Kaplan-Meier method was used to evaluate overall survival (OS) and local control (LC). Independent t-test was used for correlations between groups. RESULTS: 29 patients (31 lesions) were identified; 13 patients (15 lesions) underwent SF-SRS and 16 patients (16 lesions) underwent MF-SRS. Median follow-up was 6.8 months (1–80.8 months). Post-SRS MRI was available for 78% of patients. Median dose was 16Gy (12–18 Gy) for SF-SRS and 24 Gy (18–30 Gy) for MF-SRS. MF-SRS was delivered in a median of 3 fractions (3–5). There was a trend toward larger mean tumor volume with MF-SRS (1.297 vs 0.302mL, p=0.055). OS was 64.8% at 6 months and 49.3% at 12 months. LC was 90.9% at 6 months and 69.9% at 12 months. LC was similar between SF-SRS and MF-SRS at 6 months (100% vs 79.5%, p=0.143) and 12 months (50.0% vs 79.5%, p=0.812). Among the 4 patients who experienced local recurrence, 3 received salvage whole brain radiation and median OS was 8.1 months after LF. Distant CNS failures occurred in 40.3% of patients at 6 months and 72.4% at 12 months. Tumor volume >0.5 mL was associated with worse LC at 6 months (64.3% vs 100%, p=0.022). One patient developed symptomatic radiation necrosis (1/29 lesions, 3.4%) after MF-SRS. CONCLUSION: SRS is a safe and effective treatment for small BSM. Outcomes were not different between SF-SRS and MF-SRS but analysis is limited by small sample size.